Gen Z Purchasing Decisions Through Brand Awareness and Consumer Preferences: The Moderating Role of Social Media Influencers - Putri, Reina Aurelia; Junipriansa, Donni (Indonesian Journal of Business and Entrepreneurship, 2026)
Background: Gen Z, a generation highly engaged with the digital world, demonstrates unique consumption behaviors shaped by various external influences. The digital lifestyle of Generation Z makes social media a key space for shaping perceptions and purchasing decisions. Purpose: This study explores the primary factors affecting Gen Z’s purchasing decisions, emphasizing the roles of brand awareness and consumer preferences. Additionally, it assesses whether social media influencers strengthen or weaken these relationships. Design/methodology/approach: This study surveyed 170 Gen Z social media users in Indonesia, using a purposive sampling method. The research instrument was an online questionnaire distributed through Google Forms, consisting of several statements measured using a 5-point Likert scale (1 = strongly disagree to 5 = strongly agree). The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.1.0.9. Findings/Result: The results show that brand awareness has a positive and significant effect on Gen Z purchasing decisions, with a Path Coefficient of 0.415 and a P-value of 0.000 (<0.05). However, consumer preferences do not significantly influence Gen Z purchasing decisions, with a Path Coefficient of -0.017 and a P value of 0.777 (> 0.05). Meanwhile, the social media influencers variable has a positive and significant influence on Gen Z purchasing decisions, with a Path Coefficient value of 0.387 and a P value of 0.000 (<0.05). Conclusion: The research finds that in the digital age, Gen Z is more influenced by brand exposure and influencers than by personal preferences, reflecting a shift from individual-based decisions to consumption patterns shaped by digital communities. Originality/value (State of the art): This research contributes to businesses by creating brand awareness and understanding Gen Z consumer preferences, as well as the role of social media influencers as a strength/weakness in shaping brand awareness and consumer preferences, especially in the context of social media Keywords: brand awareness, consumer preferences, Gen Z purchasing decisions, social media influencers, influencer marketing